DEVELOPMENT AND IN VITRO EVALUATION OF 5-FLUOROURACIL NANOPARTICLES BY SALTING OUT TECHNIQUE - PB, SAILAJA; JYOTHI B, JEEVANA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: At the current miserable state of the prevalence of cancers, there is a need for the development of simple technologies to prepare formulations of anticancer drugs with less economy and investment. Hence, the aim of the present work is to prepare nanoparticles of 5-fluorouracil (5-FU) by simple technique, such as salting out method. Methods: Nanoparticles containing 10 mg of 5-FU were prepared by salting out method using Eudragit-100 as polymer. The prepared nanoparticles were evaluated by particle size, zeta potential, in vitro drug release studies, and drug-excipient interaction studies. Results: Nanoparticles prepared by salting out methods showed higher dissolution rate for formulation F3 and F5 revealed high percentage release of 98.6±0.24 in 60 min and 86.5±0.39% in 120 min. Fourier transform infrared (FTIR) spectra revealed no interaction between drug and excipients used for preparation. Conclusion: 5-FU nanoparticles can be produced successfully by salting out method using drug to polymer (Eudragit S-100) ratio of 1:3 to possess ideal drug release characteristics and average particle size of 205.1 nm.